Remote Query Resonant-Circuit Sensors for Monitoring of Bacteria Growth: Application to Food Quality Control - Leonidas G. Bachas; Libby G. Puckett; Craig A. Grimes; J. Samuel Bitler; Keat Ghee Ong (Sensors, 2002)
This paper presents a technique for in-situ remote query monitoring of bacteria growth utilizing a printed thin or thick-film sensor comprised of an inductor-capacitor (LC) resonant circuit. The sensor, which is placed within the biological medium of interest and remotely detected using a loop antenna, measures the complex permittivity of the medium. Since bacteria growth increases the complex permittivity of a biological medium the LC sensor can be used to determine bacteria concentration. This paper presents results on monitoring of three different bacteria strains, Bacillus subtilis, Escherichia coli JM109, and Pseudomonas putida, demonstrating application of the sensor for monitoring bacteria growth in milk, meat, and beer. Due to its low unit cost and remote query detection, the sensor is potentially useful for commercial scale monitoring of food quality.